Factors affecting Malaysian teenagers influence towards family purchase decision of portable playstation (PSP) / Dr. Amily Fikry @ Aziz and Mohd Reeza Bustami - Fikry @ Aziz, Amily; Bustami, Mohd Reeza (2011)
The study of family decision making usually ignored the influence of children such as teenagers. Teenager's characteristic makes them an attractive market segment for marketers and advertisers. Teenagers spend a lot of their parent's money for a certain ; category of products such as VCRs, autos, computers, stereos and sporting equipment (McLaughlin, 2000) due to the trust and busy lifestyle of their parents (Brazil, 1999). Parents also perceive that their teenagers have higher consumer skills, are more rational, and could comprehend basic economic concepts (Brazil, 1999; Roedder, 1981) as compared to younger children who are below the teen's age group. Due to that, this research attempts to fill some of this theoretical gap by focusing on the extent of relationship, if any, between teenager's resources, teenager's demographic characteristics, parental styles and family purchase decision. The objectives of this research are l) To determine the relationship between teenager's resource/s and family purchase decision, 2) To determine the relationship between teenager's demographic characteristics and family purchase decision, and 3) To determine the relationship between parental style and family purchase decision. Six hypotheses were developed to analyzed objectives of the research. This study focus on a group of teenagers in academic schools (in the age of 13 till 17 years old) who have portable Sony play station (PSP), located in Selangor and Federal Territory of Kuala Lumpur in Malaysia. Stratified disproportionate random sampling is used, with bilingual questionnaires were used to aid students in understanding and answering the questions provided in the questionnaire. Questionnaires were manually distributed to 150 students and collected by the researcher in order to obtain their influence on family purchase decisions. The findings revealed that onJy two hypotheses were supported, i.e. teenager's importance has a significant effect on family purchase decision and teenager's gender has a significant effect on family purchase decision. The remaining four hypotheses are not supported. Finally, conclusions and recommendations were derived.